The Efficacy Potential of Cyber Security Advice as Presented in News Articles - Quinlan, Mark; Ceross, Aaron; Simpson, Andrew (Interacting with computers, 2025)
Abstract Cyber security advice is a broad church: it is thematically expansive, comprising expert texts, user-generated data consumed by individual users via informal learning and much in-between. While there is evidence that cyber security news articles play a role in disseminating cyber security advice, the nature and extent of that role are not clear. We present a corpus of cyber security advice generated from mainstream news articles. The work was driven by two research objectives. The first objective was to ascertain what kind of actionable advice is being disseminated; the second was to explore ways of determining the efficacy potential of news-mediated security advice. The results show an increase in the generation of cyber security news articles, together with increases in vocabulary complexity and reading difficulty. We argue that these could present challenges for vulnerable users. We believe that this corpus and the accompanying analysis have the potential to inform future efforts to quantify and improve the efficacy potential of security advice dissemination.